Strategi Implementasi Business Process Management yang Efektif - Jeni Susyanti; Ronaldus Ledo (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Business Process Management (BPM) is a systematic approach to improving the efficiency and effectiveness of an organization's business processes. This article aims to examine effective BPM implementation strategies in organizations, including an understanding of BPM theory, methodological approaches, and key success factors. Through literature studies and qualitative analysis of several case studies of companies in Indonesia, it was found that the success of BPM implementation depends on management support, use of technology, employee involvement, and suitability of processes with the company's strategic goals. It is hoped that these findings can become a practical reference for organizations that want to implement BPM optimally.